2017
DOI: 10.1038/ncomms15491
|View full text |Cite
|
Sign up to set email alerts
|

Giant electron-hole transport asymmetry in ultra-short quantum transistors

Abstract: Making use of bipolar transport in single-wall carbon nanotube quantum transistors would permit a single device to operate as both a quantum dot and a ballistic conductor or as two quantum dots with different charging energies. Here we report ultra-clean 10 to 100 nm scale suspended nanotube transistors with a large electron-hole transport asymmetry. The devices consist of naked nanotube channels contacted with sections of tube under annealed gold. The annealed gold acts as an n-doping top gate, allowing coher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
(129 reference statements)
0
10
0
Order By: Relevance
“…The length of the naked graphene channel is defined by gold films directly deposited on top of exfoliated graphene. It was previously reported that such gold films, after annealing, can dope the graphene underneath without disrupting its ballistic transport 32,33 . These gold-covered graphene regions act as contacts to the naked graphene channel.…”
Section: Platform For Qtse In 2d Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The length of the naked graphene channel is defined by gold films directly deposited on top of exfoliated graphene. It was previously reported that such gold films, after annealing, can dope the graphene underneath without disrupting its ballistic transport 32,33 . These gold-covered graphene regions act as contacts to the naked graphene channel.…”
Section: Platform For Qtse In 2d Materialsmentioning
confidence: 99%
“…These gold-covered graphene regions act as contacts to the naked graphene channel. Few-nm sharp p-n junctions form between these graphene contacts and the naked channel 32,33 . The large aspect ratio of the channel W/L 1 ensures that quantum transport is not affected by the atomic disorder at the edges of the exfoliated crystal, such that a smooth boundary condition in the y-direction is justified 30 .…”
Section: Platform For Qtse In 2d Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theory says that metallic nanotubes can develop a band gap due to symmetry breaking of the underlying graphene lattice from strains, twists and curvature. The magnitude of this gap is predicted to be around tens of milli-electron volts but zero field gaps of an order of a magnitude larger have been reported [19][20][21]. Perhaps most intriguingly though, in the single particle picture, these gaps should vanish at the Dirac field as the nanotube quantization line is pushed to the Dirac point of the underlying graphene band structure resulting in a truly metallic nanotube.…”
mentioning
confidence: 96%